IOT-based fertigation system / Mohamad Amir Furqan Darus - Darus, Mohamad Amir Furqan (2024)
The Fertigation, the precise application of water and fertilizers in agriculture, has evolved with the integration of Internet of Things (IoT) technology. This abstract outlines an IoT-based fertigation system, focusing on key components like the ESP32 (ESPDuino-32), MDD3A Cytron motor driver, EC sensor, and water pump, and emphasizes its advantages.The IoT system incorporates various sensors, including those for soil moisture, temperature, humidity, nutrients, and Ph. These sensors provide real-time data about the crops’ environment, which is then sent to a central hub or cloud platform. Advanced algorithms and machine learning processes this data to determine the ideal irrigation and fertilization needs. Decision-making algorithms, considering factors like plant type, growth stage, and soil conditions, guide the system in adjusting solenoid valves through the MDD3A Cytron motor driver and the water pump for precise delivery.The ESP32 (ESPDuino-32) acts as the central controller, managing data acquisition and communication with the cloud platform. It integrates the MDD3A Cytron motor driver for water pump control and the Ph sensor to monitor soil acidity or alkalinity. Using advanced algorithms and machine learning techniques, the system nalyses the collected data to determine optimal irrigation and fertilization requirements. Decision-making algorithms consider factors such as plant type, growth stage, soil composition, and environmental conditions. Based on these insights, the system automatically adjusts the irrigation and fertilization processes by controlling actuators such as solenoid valves or pumps.